Penguatan Kompetensi Guru Pembina Olimpiade MIPA melalui Program Pengabdian kepada Masyarakat di Kabupaten Barru - Nurul Mukhlisa; Kamaruddin Hasan; Mansyur; Zaid Zainal; Wawan Krismanto (Jurnal Abdi Masyarakat Pendidikan, 2026)
This community service activity aims to improve the competencies of science and mathematics Olympiad coaches in Barru Regency through training and mentoring programs. The activity was held at the Barru Regency Education Office and involved elementary and junior high school teachers from various subdistricts. Participants were grouped by educational level and subject area—specifically mathematics and science—to ensure the training content was tailored to the specific needs of Olympiad coaching. The five-day training utilized a combination of lectures, discussions, problem-solving practice, and mentoring. The training materials were aligned with the MIPA Olympiad guidelines, covering concept reinforcement, problem-solving strategies based on Higher-Order Thinking Skills (HOTS), and systematic student coaching techniques. Activity evaluation was conducted through pre-tests, post-tests, observation of participant activities, and participant response questionnaires. The results of the activity showed an improvement in teachers’ understanding and skills in solving and designing HOTS-based problems. Additionally, participants demonstrated enthusiasm and active participation throughout the program. Conducting the training separately by subject area and school level was a key strength of the program, as it allowed for more focused and participant-centered instruction. Consequently, this community service initiative successfully contributed to strengthening the competencies of MIPA Olympiad coaches in Barru Regency.